DOI: 10.11606/d.22.2013.tde-12062013-151403
|View full text |Cite
|
Sign up to set email alerts
|

Mensuração e análise do tempo de assistência de enfermagem direta e indireta em Unidade de Terapia Intensiva

Abstract: DEDICATÓRIAÀ Deus por todas as alegrias, pela saúde e por iluminar e guiar meu caminho. Obrigada pelas pessoas que colocou em minha vida, principalmente a minha filha Alícia.Ao meu marido Ricardo pela paciência, pelo amor, apoio e incentivo, por caminhar junto comigo nesta jornada, sendo meu ombro amigo nos momentos de desespero.Aos meus pais, Paulo e Elza, pelo amor e carinho, por tudo aquilo que me ensinaram para que me tornasse a pessoa que sou hoje. Mãe obrigada pelas orientações e pelos momentos de desaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…The analysis of demographic and clinical characteristics revealed that age (14,15) , origin (11,17) , type of hospital stay (18) , length of stay (11,14) , and mortality (11,15) in the present study corroborate national and international literature. Divergent results were found regarding gender (11,17) , which reinforces the idea that women seek healthcare services more often, including in the oncological area.…”
Section: Discussionsupporting
confidence: 88%
“…The analysis of demographic and clinical characteristics revealed that age (14,15) , origin (11,17) , type of hospital stay (18) , length of stay (11,14) , and mortality (11,15) in the present study corroborate national and international literature. Divergent results were found regarding gender (11,17) , which reinforces the idea that women seek healthcare services more often, including in the oncological area.…”
Section: Discussionsupporting
confidence: 88%
“…These factors increase the risk of development of IAD, since patients who use beta-blockers and sedatives have reduced cognitive state and hence are more likely to develop IAD compared to patients who do not use sedatives. However, a study that measured the time of nursing care devoted to patients in intensive care found that patients in isolation who are given hypnotics/ sedatives, antipsychotic and beta-blocker drugs require more care time (18) . This may justify the results found, since it is assumed that the longer time spent by the nursing staff stays with these patients will result in the provision of more care related to the maintenance of the integrity of the skin of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Los hallazgos señalan que las características sociodemográficas y clínicas, la duración de la estadía en la UCI, la mortalidad y la gravedad del paciente son factores asociados con la alta carga de trabajo del equipo de enfermería (3,6) . Así, los indicadores de demanda de atención son cada vez más necesarios en el área de enfermería, ofreciendo una atención segura tanto para pacientes como para profesionales (7) . Sobre la base de los hallazgos de otros estudios y la importancia de la evaluación sistemática de la carga de trabajo de enfermería, la pregunta es: ¿cuál es la carga de trabajo de enfermería requerida por pacientes adultos durante su estadía en una UCI?…”
Section: Introductionunclassified